2021
DOI: 10.1007/s13300-021-01011-3
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Improves Liver Steatosis and Fibrosis in Patients with Non-Alcoholic Fatty Liver Disease and Type 2 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Introduction To evaluate the efficacy of empagliflozin compared to pioglitazone in patients with non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2DM). Methods In this prospective randomized, double-blind, placebo-controlled trial, we assigned 106 patients with NAFLD and T2DM to receive empagliflozin 10 mg ( n = 35), pioglitazone 30 mg ( n = 34), or placebo ( n = 37) for 24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 80 publications
6
99
0
5
Order By: Relevance
“…There was a significant decrease in HBA1c, FBS, and PPBS in the present study; the mean differences were 0.6, 32.88, and 64.83 respectively (p=0.000). A similar study by Chehrehgosha et al also showed a significant drop in HbA1c, FBS, and PPBS (p<0.001) [ 16 ]. A study by Kuchay et al has also reported similar results [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There was a significant decrease in HBA1c, FBS, and PPBS in the present study; the mean differences were 0.6, 32.88, and 64.83 respectively (p=0.000). A similar study by Chehrehgosha et al also showed a significant drop in HbA1c, FBS, and PPBS (p<0.001) [ 16 ]. A study by Kuchay et al has also reported similar results [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…A similar finding was noted in a study by Shimizu et al where there was a significant decrease in CAP from 314 ± 61 to 290 ± 73 dB/m (p=0.0424) [ 15 ]. Studies by Chehrehgosha et al and Taheri et al have also shown a reduction in CAP values [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, SGLT2i reduced liver fat, assessed by MRI or a controlled attenuation parameter (CAP), liver transaminases and markers of liver fibrosis (assessed by fibrosis scores or transient elastography) in patients with NAFLD and T2DM [3,5]. Among the SGLT2i, empagliflozin has been evaluated in several randomized controlled trials [8][9][10] and has been shown to reduce liver fat and liver stiffness measurements [8][9][10]. Interestingly, empagliflozin exerted these beneficial effects on the liver status in patients with T2DM even when they had excellent glycemic control and a short known disease duration [9], suggesting that its effects may be, at least partially, independent of glycemic status.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates and screening the titles and abstracts for irrelevant studies based on the topic or research type, 27 studies were selected for the full-text review. In the end, 20 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were included in our meta-analysis, including 15 RCTs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (two were three-arm RCTs [15 , 20] and one was a four-arm RCT [23] ). Supplementary Figure 1 shows the flow chart of the review.…”
Section: Baseline Characteristicsmentioning
confidence: 99%